Puerperal women's knowledge on newborn's body hygiene - Maria Paula Custódio Silva; Luciana Mara Monti Fonseca; Mariana Torreglosa Ruiz; Gilberto Pereira de Araújo; Jesislei Bonolo do Amaral Rocha; Divanice Contim (Instituto Materno Infantil de Pernambuco, 2023)
Abstract Objectives: to identify puerperal women's knowledge attending the housing unit at a teaching hospital about newborn body hygiene after receiving routine guidance from the nursing team. Methods: cross-sectional study, carried out with 207 puerperal women from a teaching hospital in the Minas Gerais State between December 2018 and May 2019. For data collection, an instrument was built and validated following three phases and descriptive statistics and linear correlation were used of Spearman's, with a confidence level of 95% for knowledge analysis. Results: 207 puerperal women participated in the study, with a mean age of 27 ± 6.3 years. Inadequate knowledge was observed, mainly regarding the sequence of cleaning the face and scalp, adequate products and hygiene of the nose, ear and mouth. The domain "before the bath" presented the highest average percentage of correct questions (94.0%±10.1), including care with the environment, temperature and intimate hygiene. Conclusion: the identification of inadequate knowledge about the newborn's body hygiene raises the need for constant and more effective guidelines, with the use of active methodologies starting in prenatal care.